Porous Functionalized Covalent-Triazine Frameworks for Enhanced Adsorption Toward Polysulfides in Li-S Batteries and Organic Dyes - Liu, Qianhui; Yang, Shuhao; Repich, Hlib; Zhai, Yixuan; Xu, Xiaosa; Liang, Yeru; Li, Hejun; Wang, Hongqiang; Xu, Fei (Frontiers in Chemistry, 2020)
Incorporation of functional building blocks to construct functionalized high porous covalent triazine frameworks (CTFs) is essential for emerging adsorptive-involved field. Herein, a series of amide functionalized CTFs (CTF-PO71) were synthesized using a bottom-up strategy, in which pigment PO71 with amide group is employed as monomer under ionothermal condition with ZnCl2 as solvent and catalyst. And the pore structure can be controlled by the amount of ZnCl2 to monomer ratio. Benefitting from the high porous structure and amide functionalities, CTF-PO71, as sulfur cathode host, simultaneously demonstrates physical confinement and chemical anchoring of sulfur species, thus leading to superior capacity, cycling stability, and rate capability in comparison to unfunctionalized CTF. Meanwhile, as adsorbent of organic dye molecules, CTF-PO71 was demonstrated to form strong chemical interaction with dye molecules, facilitating adsorption kinetics thereby promoting the adsorption rate and capacity. Furthermore, the dynamic adsorption experiments of organic dyes from solutions showed selectivity/priority of CTF-PO71s for specific dye molecules.